The voting wars : from Florida 2000 to the next election meltdown - Hasen, Richard L. (Yale University Press, 2012)
In 2000, just a few hundred votes in the state of Florida separated Republican presidential candidate George W. Bush from his Democratic opponent, Al Gore. The outcome of the election rested on Florida's 25 electoral votes, and legal wrangling continued for 36 days. Then, abruptly, one of the most controversial Supreme Court decisions in U.S. history, Bush v. Gore, cut short the battle. Since then we have witnessed a partisan war over election rules. Election litigation has skyrocketed, and election time brings out inevitable accusations by political partisans of voter fraud and voter suppression. Richard L. Hasen, a respected authority on election law, chronicles and analyzes the battles over election rules from 2000 to the present from a nonpartisan standpoint. He explains why future election disputes will be worse than previous ones--more acrimonious, more distorted by unsubstantiated allegations, and amplified by social media.--From publisher description.